Role of Teachers in Fostering the Reading Habits of Grade 1 Students - Nia Hidayatul Maulana; Asih Rosnaningsih; Sumiyani Sumiyani (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2022)
The Role of Teachers in Developing Reading Habits for Class 1 Students at SDN Karawaci Baru 4 Tangerang City". Thesis. Department of Elementary School Teacher Education, Faculty of Teacher Training and Education, Muhammadiyah University Tangerang 2018. The role of schools and parents is very important in supporting children's activities to improve reading habits. Improving reading habits, the most strategic way to form students' reading habits in the school environment and in the community. This study aims to determine the teacher's role in growing the reading habits of grade 1 students at SDN Karawaci Baru 4 Tangerang City. The research method used is descriptive qualitative with data collection techniques used include observation, interviews and documentation. Based on the five teacher roles, it can be concluded that two roles have been carried out well, namely the teacher's role as a motivator and the teacher's role as a facilitator. Meanwhile, the three roles cannot be carried out optimally, namely the role of the teacher as an innovator, the role of the teacher as an inspiration and the role of the teacher as a mediator. The teacher's role as a motivator and facilitator is considered good because it is proven that the teacher provides verbal encouragement in the form of words of encouragement for students, reminds the importance of reading, provides additional value for students, there is a reading corner provided for students, freedom in borrowing books. in the library, habituation of reading activities 15 minutes before the learning process, as well as providing good reading techniques. This is inversely proportional to the teacher's role as an innovator, inspiration and mediator which is still lacking in helping students grow students' reading habits